Development and psychometric evaluation of the nursing home accreditation scale: A methodological study - Ali Jadidi; Banafshe Samari; Ali Faal Araghi Nejad; Leili Tapak; Masoud Khodaveisi (Elsevier, 2024)
Background: Standard nursing homes (NHs) are currently a major healthcare need in all societies due to the increasing number of elderly people. There is no valid and reliable instrument for NH accreditation in Iran. Therefore, the present study was conducted to develop and psychometrically evaluate the Nursing Home Accreditation Scale (NHAS) for the accreditation of NHs in Iran. Methods: This cross-sectional methodological study was conducted in 2020 in Hamadan, Iran, in two phases. In the first phase, NHAS was developed through reviewing the existing literature. In the second phase, NHAS was used in five NHs and the collected data were used to assess its validity and reliability through calculating content validity ratio and index, Cronbach's alpha, and intraclass correlation coefficient. Data were analyzed using the SPSS software (v. 26.0). Findings: The primary NHAS had 112 items. Fourteen items were deleted due to content validity ratios less than 0.51 and the content validity ratios and indices of the remaining 98 items were more than 0.51 and 0.79, respectively. The Cronbach's alpha and the intraclass correlation coefficient of NHAS were 0.78 and 0.81, respectively. Conclusion: The 98-item NHAS is a valid and reliable instrument for NHs accreditation. This scale can be used to determine and prevent risks and injuries in NHs, improve the conditions of elderly people's residence, and improve the quality of services in NHs.